Coercion, Control, and Cooperation in a Prostitution Ring. Issue 1 (May 2014) - Morselli, Carlo; Savoie-Gargiso, Isa
Coercion and control are key components of the dominant narrative on sex trafficking, but the power and exchange relations between some of the key players in trafficking have not been carefully examined. This study is based on electronic surveillance data from a two-year police investigation of a prostitution network in Montreal. All of the prostitutes in the network had initially been recruited when they were minors. Whereas most of the writing on sex trafficking portrays pimps as being involved in highly exploitative and coercive relationships with prostitutes, we found that control was not always the sole purview of the pimps, that prostitutes often held key positions and privileged roles within the network, and that pimps' and prostitutes' relationships involved complex exchanges of network resources.